COMMUNITY BASED EMPOWERMENT: STUDI PADA KELOMPOK USAHA BERSAMA “SEDAP MELATI” DI DUSUN BABADAN, SITIMULYO, PIYUNGAN, BANTUL, YOGYAKARTA - Sulistyaningsih Sulistyaningsih; Achmad Zainal Arifin; Dadi Nurhaedi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
This study aims to determine the efforts of a small Entreprise of Sedap Melati in resolving some problems related to the issue of developing its productive process. Two theories used in this study, which are communication action theory of Habermas and empowerment of If’s theory. The method used in this study is a qualitative research method using a Participatory Action Research (PAR) model. To collect the data, several methods are used including: observation, interviews, FGD (Focus Group Discussion) and documentation. Interpretative methods of data analysis is done by comparing, sifting through and combining various data residing in the same context, the audit trial (checking the raw data, analyzing them, and making conclusions process) as well as a review by related parties are seriously considered. The results show that Kube Sedap Melati has facing some serious constraints in its development, such as the issue of human resources, marketing, and infrastructure facilities. Some efforts have been undertaken by Kube Sedap Melati to overcome these problems. For the issue of transportation, for example, members of Kube Sedap Melati agrred to hire transports to deliver their products to consumers. They also aware of the needs of having a better promotions, including the use of internet and social media. Based on the analysis using communication actions’ theory of Habermas, there is a necessary for all members of Kube Sedap Melati to establish an open communication between members and administrators, either in a formal or informal ways. Mutual trust among the members is essential in order to overcome their human resource problem. In the context of empowerment, Kube Sedap Melati can actualize in three sides: fist, to create a conducive atmosphere to develop and maximize their potentials; second, to strengthen their competitiveness to other similar enterprises; and third, to protect a strong group and prevent unhealthy competition among them. Other potentials that need to be considered is to include religious practices and traditions of the community as an important source of income through providing some snacks and foods in every religious events or traditions conducted by members of community